الأهمية الاقتصادية لمساهمة الإمكانيات الموردية للقطاع الزراعي في نمو الاقتصاد المصري - غانم، عادل محمد خليفة; التطاوي، نشوى عبدالحميد; قمره، سحر عبدالمنعم السيد (الجمعية المصرية للإقتصاد الزراعي, 2020)
استهدف هذا البحث تقدير مساهمة الموارد الاقتصادية الزراعية في نمو الاقتصاد المصري، باستخدام التحليل الاقتصادي القياسي. وأوضحت الدراسة أن مساهمة الموارد المائية احتلت المرتبة الأولى، تليها كل من المساحة المحصولية والعمالة والاستثمارات الزراعية على التوالي. وتراوحت مساهمة القطاع الزراعي في معدل النمو الاقتصادي بين حد أدنى بلغ ۰,۰۹% وحد أعلى بلغ ۱,۲۱% عند درجة ثقة ٩٥%. ولزيادة مساهمة القطاع الزراعي في إجمالي الناتج المحلي ومعدل النمو الاقتصادي، توصي الدراسة بضرورة تطوير نظم الري في الأراضي القديمة وتبطين الترع والمصارف، ضخ مزيد من الاستثمارات الزراعية، ضرورة التوصل لاتفاق قانوني بين مصر وإثيوبيا والسودان بشأن ملء وتشغيل السد الأثيوبي والحفاظ على حصة مصر من مياه نهر النيل. The research aimed to estimate the contribution of agricultural economic resources to agricultural output, GDP, and the rate of economic growth in Egypt during the period 1990-2019. In achieving its objectives, this study relied on econometric analysis. This study revealed that a decline in the agricultural sector’s contribution to GDP at an annual rate of 1.7%, due to the decline in the share of the agricultural sector in employment, investments and available water resources. Water resources ranked first in the extent of their contribution to agricultural output and GDP, followed by cropping area, agricultural labor, and agricultural investments (public and private). The contribution of the agricultural sector to the economic growth rate ranged between a minimum of 0.09% and a maximum of 1.21% at a confidence level of 95% during the study period. The contribution of the rest of the other economic sectors to the economic growth rate ranged between a minimum of 3.22% and a maximum of 4.34% at a confidence level of 95% during the study period. In order to maintain the economic size of the agricultural sector, increase its relative share in the GDP and the rate of economic growth, the study recommends the following: (1) the need to develop irrigation systems in old areas and lining canals and drains, (2) pumping more public and private investments in the agricultural sector, (3) the necessity of reaching a legal agreement between Egypt, Ethiopia and Sudan regarding filling and operating the Ethiopian Renaissance Dam and preserving Egypt's share of the Nile water.
Keywords: التنمية الاقتصادي -- الموارد المائية -- الاستثمارات الزراعية -- نظم الري -- الاقتصاد المصري